Identifikasi Parameter Dalam Penentuan Prioritas Penangaan Masalah Sistem drainase Di Wilayah Kota Pekanbaru Menggunakan Metode Analytical Hirearcy Process (AHP) - Helfira, Nany; Fauzi, Manyuk; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pekanbaru city drainage systems generally use a gravity system that depends on the topography area. The topography that relatively flat causes the rainwater drainage system cannot occur properly. Parameter of drainage system problem handling is planned based on the decision-making system method of Analytical Hierarchy Process (AHP) which are: Technical, Economical, Environmental, and Social/Cultural. The results of the AHP analysis with using Expert Choice program 2000 found that the most influential criteria in drainage system problem handling is technical criteria, with 47.9% level of technical criteria, economical criteria 30.8%, environmental criteria 11.2%, and the social/cultural criteria 10.2%. Priority areas in the handling of the drainage system is: Purwodadi Ujung Perumahan Teratai Indah with the percentage level of 53,3%, Jalan Soekarno Hatta (Pasar Pagi Arengka intersection) 31%, and Jalan Riau Ujung (Jalan Riau Ujung – Jalan Soekarno Hatta intersection) 15,7%. The most influence sub- criteria in determining the priority handling of the drainage system are: the capacity of the drainage system network, the availability of budget to funding the annual O & M of drainage systems, coverage of area services, and management and maintenance of drainage infrastructure.Keywords : analytical hierarchy process, expert choice, priority